Pengelolaan Tanah Wakaf Untuk PCM Turi Yang Produktif dan Berkemajuan - Agus Nugroho (Universitas Lancang Kuning, 2021)
As in the other areas, the management of waqf land in PCM Turi, Sleman, DIY has not been optimal, even though it has great potential if managed properly. This is due to the knowledge, insight and skills of the PCM Turi in managing the waqf land into a productive garden and making the waqf land as a medium for da'wah is still limited. Therefore, a community service program was conducted with several methods including coordination, counseling, technology transfer, training, as well as mentoring and evaluation. The results of the community service program show that the community service program has been carried out well, with the establishment of productive fruit and vegetable gardens. PCM Turi gains knowledge and skills in managing waqf land into productive land, so that it can become a media for da'wah bil hal and become an example for the other PCMs in managing the waqf land